Pengaruh Pengetahuan Kesadaran dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan - Arrin Sulistiyowati; Rahma Putri Pramudita; Hari Purwanto; Amy Wulandari; Nur Asih Triatmaja (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Taxes are the main source of government revenue used to finance expenditures and national development. This study aims to assess the effects of knowledge, awareness, and tax socialization on the compliance of land and building taxpayers. A quantitative approach and primary data were used, with 100 respondents selected through random sampling. Data were analyzed using multiple linear regression with the assistance of SPSS 26. The results show that taxpayer knowledge has a positive and significant effect on land and building taxpayer compliance, while taxpayer awareness and tax socialization do not have an impact on the compliance of PBB taxpayers. All three variables simultaneously have a significant positive impact on mandatory compliance with PBB. The findings highlight the critical role of taxpayer education in enhancing compliance, emphasizing that informed taxpayers are more likely to fulfill their obligations. Meanwhile, simply increasing awareness or providing general socialization without targeted knowledge transfer does not guarantee improved compliance. These results suggest that policy interventions should focus on strengthening taxpayer knowledge and understanding of regulations to maximize compliance rates. Overall, the study contributes valuable insights for policymakers and tax authorities in developing effective strategies to enhance taxpayer adherence to land and building tax regulations.